Fluid Mechanics with problems and solutions, and an aerodynamic laboratory - Krause Egon (Berlin Springer-Verlag, 2005)
presents a current and comprehensive report on this emerging field that bridges the areas of geology and mechanics. It is of direct interest to a wide spectrum of earth scientists and engineers who are concerned with upper-crust mechanics and fluid movem
Keywords: Fluid mechanics